Proposal for the revision of the Special Fitness Test in judo - Blach, W.; Ambrozy, T.; Obminski, Z.; Stradomska, J.; Rydzik, L. (Journal of Kinesiology and Exercise Sciences, 2021)
Introduction: To assess the level of physical fitness among high-performance athletes, a number of tests are used, including a treadmill, cyclo-ergometer or other mechanical devices integrated with a sensitive power and work measurement system. Such studies, however, involve selected parts of the muscles of the upper or lower limbs, while the specific structure of the task in combat sports requires the work of the muscles with regard to the entire body. For this reason, a field test called Special Judo Fitness Test (SJFT) has long been used in judo. Performing this test requires the participation of 2 sparring partners (uke) with a body mass similar to the tested competitor. In small groups, this requirement may not always be met. In addition, the uke is required to be highly skilled in the safe technique of falling onto a mat (ukemi) in order to minimise the risk of injury. The aim of the work was to develop and validate a throw test with the use of dummies already available on the market. Materials and methods: The study comprised 3 competitors from each weight category. The subjects performed special fitness tests - seoi-nage throwing technique with the participation of 2 uke and the o-goshi technique (Special Fitness Test for Combat Sports - SFTCS) with the use of dummies having masses adapted to `conventionally` lighter (40-81 kg) and heavier athletes (> 81 kg). In the case of seoi-nage, the uke stood up on his own, while in the o-goshi test, the tori personally verticalised the dummy for the next action. For each test, the number of throws was recorded and the Fitness Index was calculated from the measurements of changes in the heart rate/minute after the trials were performed. The trials for both tests were carried out on 2 dates with an interval of 5 days. Using statistical calculation procedures, the results of both tests were compared and the SFTCS was validated. Results: Statistically significant linear correlation coefficients were recorded for the number of throws and the Fitness Index between both tests and the 2 terms. The calculations of the Intraclass Correlation Coefficients for repeated measures and the standard error have demonstrated the great applicative value of the SFTCS. Conclusions. SFTCS provides reliable results of physical fitness, it is easy to perform in field conditions and requires no uke involvement.